Penggantian Wali Nasab oleh Wali Hakim menurut Intruksi Presiden Nomor 1 Tahun 1991 - Ahmad Nabil Atoilah; Ahmad Kamal (Istinbath | Jurnal Penelitian Hukum Islam, 2020)
The compilation of Islamic Law (KHI) article 19 states that "marriage guardian in marriage is a pillar that must be met for the prospective bride who acts to marry her". The marriage guardian consists of two, namely the guardian of the nasab and the judge's guardian. Wali nasab is a marriage guardian based on blood relation or kinship with the bride of the father's side. While the judge's guardian is a marriage guardian appointed by the Minister of Religious Affairs or an official appointed by him, who is given the right and authority to act as a guardian. Regarding the guardian, if the guardian is not present or does not want to marry a girl under her guardianship, her marriage guardian right falls to the judge's guardian.